Chemical characterization and biological studies of Neem (Azadirachta Indica) extracts - Jessinta, Sandanasamy (2014)
Neem (Azadirachta indica) (Family: Meliaceae), also known as ‘Pokok Mambu’ in Malaysia is widely known to contain variety of bioactive compounds that had been proven for the cure of various infections and diseases related to toxicity and bacteria. The extractions of the plant constituents are mainly dependent on the extraction methods, conditions and solvents. This study aims on the extraction of the chemical constituents’ and identification of the volatile constituents of A. indica extracts. The cytotoxicity effect was studied for the extracts that lead towards the isolation of a bioactive compound. The oil of the plant was studied for its physicochemical properties and antibacterial activity. The crude extracts (barks, leaves and roots) were extracted via solvent extraction (acetone, chloroform, maceration and refluxed in ethanol), while the fractions (hexane, chloroform, ethyl acetate and aqueous) were produced from partitioning of 80% methanol crude. Seed oil was extracted via Soxhlet with hexane for six hours. Volatile compound analysis via GC-MS was performed for all crude and fractions and cytotoxicity test against brine shrimp, Artemia salina for determination of LC50 after 24 h. The isolation and identification of bioactive compound from the most active fraction of cytotoxicity were performed via preparative-HPLC, UV-Vis, IR, MS and NMR. Physicochemical properties of oil were studied according to standard methods. Antibacterial activity of oil was determined against B. subtilis, E. coli and S. aureus via well diffusion method. Yields of the extracts were varied among different parts due to polarity of solvents and extraction conditions. Highest and lowest yields of crude extracts were leaf and bark reflux in ethanol with 5.46% and 0.13%, respectively. Minimum and maximum yield was obtained for fractions by root ethyl acetate (0.06%) and leaf chloroform (1.15%). The n-hexadecanoic acid was detected in all samples with seven similar compounds in both crude and fractions as the most abundant volatile compound. Cytotoxicity proves that root acetone (457.09 ± 0.88 ppm) and leaf ethyl acetate extract (1.35 ± 0.40 ppm) are the most toxic. All the fractions and only root acetone crude extract falls under toxic level (LC50 values < 500 ppm). The partitioning to different fractions separates the complex plant constituents according to polarity that influences the cytotoxicity. The isolation of quercetin-3-O-β-D-glucopyranoside from leaf ethyl acetate proves the cytotoxic effect. Major characteristics of the oils are; density: 0.95 g/cm3; refractive index: 70.90; acid value: 4.80 mg KOH/g; free fatty acid (oleic): 4.75 %; iodine value: 93.09 gI2/100g; pH: 4; peroxide value: 8.49 meq O2/kg; moisture & volatile matter: 0.83 % and unsaponifiable matter: 1.84 %. The major fatty acid chains in the oil are; linoleic-: 34.69 %; oleic-: 20.46 %, stearic-: 20.42 % and palmitic acid: 18.66 %. Inhibition zone for antibacterial study with 20, 40, 60 and 80% of oil lies between 1.23 ± 0.03 to 1.70 cm, 1.33 ± 0.06 to 1.6 ± 1.57x10-16 cm and 1.4 ± 0.03 to 1.63 ± 0.03 cm for B. subtilis, S. aureus and E. coli, respectively. The MIC was 0.63± 0.0002, 2.50± 0.0010 and 5.00± 0.006% for B. subtilis, E. coli and S. aureus, respectively and S. aureus is more resistant. Results obtained supports that A. indica plant has high advantage to be used as drug in chemical and pharmaceutical industries. The study should be further continued through direct study with insect and human cell line to confirm the effect of the drug